Entre o discurso e a prática: há reforma?: uma reflexão sobre práticas interventivas de cuidado na clínica da saúde mental - Silva, Maura Lima Bezerra e (2006)
The purpose of psychiatric reform is to introduce a radical change in asylum practices. This means the reform adopted another form of thinking madness, psychic suffering and assistance/care; in other words, it means build new paradigms and new references to guide the interventions in mental health. The compromise with reform s logic implies in a constant exercise of a systematic revision of care practices, so there are not the risk of repeating the old habits more than deconstructing them. The main intention of this research was to watch if the practices of mental health care are related with the logic and paradigms proposed by the reform. This observation was developed in accordance with a methodology clinicfenomenologic and implemented with the means of participant observation, being the data build based on our experience inside a municipal health care service, specifically the Blue Space Psychosocial Attention Center, which has the conception of reform as a background. The fenemenologic basement made emerge from the data, put together in an Observation Diary, four categories that showed in what measure the actions of care in the service came close to the reform s ethic, in what measure they got far, the operational mode of the service/team concerning to the exercise of care and the mode of relationship of the researcher with the service. The conclusion was that practices of care developed in service both signalized to approximations with the reform s ethic, as with separation, reflecting an oscillating practice, nevertheless a tendency to depart have been more strong. It was noticed that between the desire of taking care of the team and the actions pointing to the depart of reform s ethics there was a space filled by affective states of loss of heart and tiredness which showed about the experience of psychic suffering of the team. A more careful observation pointed a recent service s municipalization as a factor of changing felt as a traumatic mark. This way, that departure was understood both as a form of the team protect itself to fulfill the empty felt as incautiousness, as of the team signalize its pain and ask intervention and care for its own, so they can develop correctly their work of team-care